Pattern of Alcohol Consumption and its Effects on Livelihood in Selected Rural Communities of Enugu State, Nigeria - M. U., Ng’en Dimelu; C. , Agbo; E. M. , Igbokwe (Asian Journal of Agriculture and Rural Development, 2011)
The study examined alcohol consumption and its effects on economic and social livelihood of selected rural communities of Enugu State. One hundred and twenty randomly selected alcohol consuming heads of households and sixty four purposively selected non-alcohol consuming heads of household were used. Data were collected using structured interview schedule and analysed using percentage. Alcoholic beverages available were palm wine (100%), beer (100%), local gin (100%), spirit (89.2%), and burukutu (41.7%). Respondents indicated preference for palm wine (50.0%). Choice of alcoholic beverage was a function of several factors namely availability, ability to produce the alcohol, cost and others. Effects of alcohol consumption were evident by less commitment to livelihood activities, household’s welfare, incidents of violence and others. The study recommends that policies should be enacted to regulate proliferation and operation of alcohol enterprises in the rural areas. More importantly is the regulation of the type of alcohol marketed in the communities. Also government should promote programmes that target improved livelihood strategies and empowerment of rural people to enhance diversification of the rural economy.